Assessing the significance of ESP instruction in engineering education: evidence from student perspectives - Khabirova, Zulfiya Anvarbekovna (The Lingua Spectrum, 2026)
This study explores the effectiveness of English for Specific Purposes (ESP) instruction among second-year Electrical Engineering and Computer Engineering students at Ajou University in Tashkent. Using an IMRAD framework, the research integrates survey and interview data to analyze students’ perceptions, motivation, and learning outcomes. A total of 37 students participated, while 36 completed a structured questionnaire. Participants were aged 18–22 with B1–B2 English proficiency levels. Empirical analysis revealed that 74% of students considered ESP essential for their future careers, while 96% positively evaluated project-based and case-study activities for improving technical vocabulary acquisition. Descriptive statistical analysis and thematic coding of interviews indicated increased engagement, improved comprehension of technical terminology, and enhanced communicative competence. Moreover, the findings support learner-centered ESP design and demonstrate that contextualized instruction significantly contributes to professional readiness. As well as, the study contributes to ESP pedagogy by providing evidence from Central Asian higher education contexts.